Pengembangan Permainan Puzzle Awan Berbasis Android Dalam Pembelajaran FPB DAN KPK - Agnes Putri Ayu Wanlin; Tatik Retno Murniasih; Rosita Dwi Ferdiani (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This study aims to develop a puzzle game based on aspects of validity, accuracy and effectiveness. Cloud puzzle game is a learning media that can support the learning process. A puzzle game containing FPB and KPK material that learns about the meaning and steps to determine FPB and KPK.This study uses the ADDIE development model. The steps for developing this learning media are through 5 stages: (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. This study involved 19 students of class VII SMP Negeri 02 Wagir and 9 students of class VII SMP Negeri 02 Wagir as test subjects for cloud puzzle games, as well as lecturers and teachers as experts in cloud puzzle game validators. Questionnaires were used for material experts, media experts, and learning experts to test the validity of cloud puzzle games, user response questionnaires (teachers and students) were used to test the feasibility and effectiveness of cloud games.The results of this study are: (1) Material validation results 3.5, media validation results 3.53 and learning validation results 3.75 with the "very valid" category. (2) The results of the cloud puzzle game on the user (teacher) response were 3.92, the result of the student user response for the limited field trial was 3.78 and the result of the student user response questionnaire for the broad field trial was 3.52 with the "very feasible" category. (3) The results of the effectiveness of the cloud puzzle game on the user (teacher) response were 3.92, the result of the student user response for the limited field trial was 3.78 and the results of the student user response questionnaire for the broad field trial were 3.52 with the "very effective" category.